Anesthesia considerations for patients with narcolepsy. - Joyce JA (AANA Journal, 1999)
Narcolepsy is a derangement of the normal sleep-wakefulness rhythms. Originally, narcolepsy was thought to be a form of epilepsy; however, with the development and subsequent refinement of the electroencephalograph, this notion is no longer accepted. The disorder is characterized by inappropriate intrusions of rapid eye movement sleep into the wakeful state and multiple disruptions of the sleep cycles. Narcolepsy usually has its onset anytime between the ages of 10 years and 50 years, with the greatest majority of patients first reporting noticeable symptoms between the ages of 15 and 35 years. Patients with narcolepsy may exhibit excessive daytime sleepiness, cataplexy, hypnogogic and/or hypnopompic hallucinations, and sleep paralysis. The cause of narcolepsy is presently unknown. Recent research has identified a possible genetic contribution via chromosome 6, but some form of environmental influence appears to be necessary for the disorder to be manifested. There is no cure for narcolepsy; however, symptomatic relief may be achieved through a trial-and-error combination of amphetamines and tricyclic antidepressants. The nature narcolepsy often forces the individual to undergo some rather dramatic lifestyle changes and can lead to the development of other associate disorders, such as depression and obesity.